Prevalence of Gastrointestinal Helminthiasis in Horses and Donkeys of Hawassa District, Southern Ethiopia - Mesfin Mathewos; Dawit Girma; Haben Fesseha; Metages Yirgalem; Eyob Eshetu (Veterinary Medicine International)
Background. Gastrointestinal helminth parasite infection is a major influencing factor against the profitability of working equines all over the world. Methods. A cross-sectional study was conducted to determine the prevalence of gastrointestinal tract (GI) helminths and assess the associated risk factors in donkeys and horses in the Hawassa district. A total of 214 fecal samples were collected from randomly selected equines (112 donkeys and 102 horses) and examined for the presence of eggs of GI helminths using standard coprological techniques. Results. According to the current study, the prevalence of GI helminths in equine was 78.5% (168/214) and the highest prevalence was reported in donkeys 92% (103/112) as compared to horses 63% (65/102). Out of 168 positive samples, the different species of parasites were identified, namely, Strongyle species 120 (56.1%), Strongyloides westeri 76 (35.5%), Parascaris equorum 54 (25.2%), Anoplocephala perfoliata 34 (15.8%), Oxyuris equi 20 (9.3%), Fasciola hepatica 18 (8.8%), Gastrodiscus species 12 (5.6%), and Dictyocaulus arnfieldi 4 (1.8%). There was a strong association between the prevalence of GI helminths and factors such as the species of equine, body condition scores, and feed type (p < 0.05). However, no significant association (p > 0.05) was observed between the prevalence of GI helminths and putative risk factors such as age, sex, housing, and water source. The coproculture performed on 30 pooled fecal samples revealed that Cyathostomes species, Strongylus vulgaris, and Strongylus edentatus were the major helminth parasites of donkeys and horses. Conclusion. The frequency of gastrointestinal helminths in equine species was high, especially in donkeys. Hence, strategic deworming using broad-spectrum antihelminthic drugs and a rotational grazing program should be implemented to control and prevent the diseases.